Nursing Care in Post SC Patients with Intervention Application of Foot Massage Therapy: Case Study - Mara, Maria Fransiska; Cunha, Theresia Syrilla da (Universitas Muhammadiyah Lamongan, 2023)
Introduction: Sectio caeasar is labor by making an abdominal incision to remove the fetus. Sectio caesarea delivery is the process of removing the baby by dissecting the mother's abdomen by making an incision in the uterine wall. Sectio caesarea is the main medical action to save the life of the mother and also the baby. This study aims to describe nursing care in postpartum section caesarae mothers with the application of foot massage therapy to reduce pain.Methods: This research uses a case study design. Data collection ranging from assessment to nursing evaluation was carried out in the Anggrek room of RSUD dr. TC. Hillers Maumere in January 2023. The samples used were 2 patients who were hospitalized for at least 3 days. Data collection techniques use interviews, observations and documentation studies.Results: assessment of two respondents who were postpartum mothers through day SC to those who experienced pain during the treatment period. The diagnosis established is Acute Pain associated with Physical Injury Agents (sectio caesarea surgical procedure: disconnection of tissue incontuinity) Intervention is carried out is the application of foot massage therapy, observation of pain scales and vital signs and collaborative for further action. Evaluation after treatment pain reduced, no signs of infectionConclusion: After foot massage for 3 days for 15-20 minutes showed a decrease in search in postpartum Sectio caeasarea patientsKeywords: Foot massage, sectio caessarea, pospartum